IMF Staff papers : Volume 19 No. 1. (IMF Staff Papers; IMF Staff Papers, 1972)
This paper focuses on current issues on the transmission process of monetary policy. The main process by which monetary forces influence the real economy in Keynesian income/expenditure models is through the cost-of-capital channel. In addition to the cost-of-capital channel, post-Keynesians also recognized two other channels, namely, the wealth effect on consumption expenditure and the credit rationing linkage between the financial and real sectors. One of the most significant post-Keynesian developments has been the emphasis on net private wealth as well as income as a factor influencing real flows of expenditures. The flow of services of outside money is the saving of time in barter transactions, which stems from the role of money as a medium of exchange. The saving of time may be used either for leisure or to produce capital goods. A fundamental and basic development in monetary theory subsequent to Keynes' liquidity preference theory has been the capital theoretic formulation of the demand for money.